The Impact of TikTok Influencer Credibility and Authenticity on the Purchase Intention of UNJ Students for Promoted Products - Lailatul Isti’anah; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2026)
This research seeks to scrutinize how TikTok influencers’ perceived credibility and authenticity shape consumers’ inclination to make a purchase of Universitas Negeri Jakarta (UNJ) students toward endorsed products. The expanding use of influencer marketing on social media, particularly on TikTok, highlights the need to provide a clearer account of how influencer characteristics affect consumer behavior. Employing a quantitative research design, this study uses a survey method with respondents consisting of UNJ students who actively use TikTok and follow at least one influencer. To test the proposed research model, the data were processed using the analytical framework was operationalized using Partial Least Squares Structural Equation Modeling (PLS-SEM) within the SmartPLS platform. These findings suggest that purchase intention toward influencer-promoted products is influenced by a more complex decision-making process, where influencer credibility and authenticity may operate indirectly or in conjunction with other factors rather than as direct predictors. This study deepens the theoretical grounding of influencer marketing research by emphasizing the complex and contextual role of influencer characteristics in influencing consumer behavior on TikTok. Future research is recommended to incorporate mediating or moderating variables to better explain the mechanisms underlying purchase intention in social media contexts.